ANALYSIS OF DIFFERENCES IN STUDENT KNOWLEDGE ABOUT ENVIRONMENTAL HEALTH THROUGH PROJECT BASED LEARNING: A 21st CENTURY HEALTH EDUCATION STRATEGY - Fatria, Erian; Priadi, Agus; Fransiska, Mellia (Universitas Pakuan, 2024)
This research is motivated by the poor quality of environmental health which is associated with high population growth and environmentally irresponsible community behavior. The purpose of this study is to determine the effectiveness of the project-based learning strategy by assigning tourism environmental health videos in Bukittinggi City as outputs or course products, as well as providing information related to differences in student knowledge before and after being given environmental health lectures using project-based learning strategies. This research uses quantitative methods with a quasi-experimental approach with a one-group pretest post-test design. The data analysis technique uses a t-test against students' knowledge about environmental health. The research instrument given is in the form of a calibrated test given before and after treatment. The sample in this study was 17 students of Bachelor of Applied Health Promotion at Prima Nusantara University, Bukittinggi taken using purposive sampling. The inclusion criteria for this study sample were students in the field of health sciences who had never taken an environmental health course. Based on the analysis of research data, there were differences in student knowledge before and after being given environmental health lectures using a project-based learning strategy. In this study, it was concluded that the project-based learning strategy with the assignment of tourism environmental health videos has proven to be effective and efficient and can be considered to improve students' environmental health knowledge.